Engineering technology and application : proceedings of the International Conference Engineering Technology and Application (ISETA 2017), May 25-28, 2017, Montreal, Canada /: proceedings of the International Conference Engineering Technology and Application (ISETA 2017), May 25-28, 2017, Montreal, Canada. (2017) - Unknown
No abstract available